Regional policy, economic performance and industrial structure - Hans Maks; Maurice Oude Wansink (European Regional Science Association (ERSA), 1998)
In this paper we develop a method for the evaluation of regional economic performance based on an input-output (IO) framework. After choosing economic criteria for measuring this performance, such as real GDP per worker, we pick out the 'best'performing region per sector. Taken together, they describe an optimal regional industrial structure for all sectors, a so called 'optimal' input coefficients table. On the basis of this table, we will investigate the causes of regional convergence. Furthermore, this table can be used as a point of reference for economic policy makers at the regional level. Structural deviations from the 'optimal' industrial structure may be reasons for policy action, so that the industrial structure can be evaluated in a normative way. In this paper, we investigate those deviations for 11 regions and 29 sectors in the Netherlands for the 1980-1992 period. The central focus is on the question how regional policy makers can improve regional economic performance by adjusting the regional industrial structure.
Keywords: 330